The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1080/10428190701474357
|View full text |Cite
|
Sign up to set email alerts
|

TCR spectratyping revealed T lymphocytes associated with graft-versus-host disease after allogeneic hematopoietic stem cell transplantation

Abstract: Clonal expansion of T cells after allogeneic hematopoietic stem cell transplantation (allo-HSCT) has been observed, but their characteristics remain to be fully elucidated. We report here that CD8(+) T cells were the dominant T lymphocytes seen and T-cell repertoire diversity decreased dramatically during the first 3 months after allo-HSCT. Patients with GVHD grade II - IV had significantly lower T-cell repertoire diversity compared with non-GVHD patients. TCR beta variable gene (TCRBV) subfamily 8, 5.1, 5.2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
4
17
0
Order By: Relevance
“…153 Similar results were seen in prior studies using CDR3 spectratyping. 155,156 In contrast, another study utilizing deep sequencing methods reported that grade 2-3 acute GVHD is actually associated with a higher TCR diversity than those who developed grade 0-1 acute GVHD, suggesting that GVHD did not restrict recovery of TCR repertoire. 154 The differences noted in these studies are a reflection of different graft and donor sources, conditioning regimens and the use of T cell depletion.…”
Section: Assessment Of T Cell Receptor Repertoirementioning
confidence: 86%
“…153 Similar results were seen in prior studies using CDR3 spectratyping. 155,156 In contrast, another study utilizing deep sequencing methods reported that grade 2-3 acute GVHD is actually associated with a higher TCR diversity than those who developed grade 0-1 acute GVHD, suggesting that GVHD did not restrict recovery of TCR repertoire. 154 The differences noted in these studies are a reflection of different graft and donor sources, conditioning regimens and the use of T cell depletion.…”
Section: Assessment Of T Cell Receptor Repertoirementioning
confidence: 86%
“…Further, the dominant Vβ expansions differed amongst littermates although human PBMCs from a single donor was used for transplantation in for each experiment, which also suggests that the selection of particular Vβ was a stochastic effect and does not represent a selective outgrowth of immunodominant clones. Distinct oligoclonal T cell expansions have also been reported in human GVHD after stem cell transplantation [21, 22, 23, 24]. Whether IL-10 has a modulatory role with IL-2 in shaping the T cell repertoire in the GVHD response is not known but it is possible that increased bioavalibility of the two cytokines could influence TCR repertoire at sites of GVHD activity.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular structural analysis has revealed that CDR3 mainly recognizes MHC molecules bound to antigenic peptides [20, 21]. Hence, analysis of CDR3 can reveal changes in antigen-stimulated T cells [22, 23], the number of T cell clones, and T cell functioning [24, 25]. …”
Section: Discussionmentioning
confidence: 99%